Audiovisual Content for Children and Adolescents in Scandinavia Production, Distribution, and Reception in a Multiplatform Era - Jensen, Pia Majbritt (Nordicom, University of Gothenburg, 2023)
Scandinavian children and adolescents' media consumption has changed dramatically in the past decade. Films, series, and social media content on global platforms like Netflix, Disney+, and YouTube are now a major part of young people's media diet, while encounters with domestic films, series, and platforms are in decline, severely challenging the ways domestic players think about young audiences. The contributions in this book explore these recent developments in the production, distribution, as well as reception of fictional content for children and adolescent audiences in the thoroughly digitalised and transnationalised Scandinavian countries. Using qualitative and quantitative methods, such as interviews, case studies, textual analyses, and surveys, the contributors present recent studies on how commissioners and producers develop children's content in the highly competitive, professionalised, and digitalised media environment, and on how children think about Scandinavian vis-à-vis global content. Collectively, the book offers readers new knowledge on how Scandinavian media distributors, producers, and creatives - and their young audiences - act in the face of this new reality. This book is relevant for scholars, students, and industry professionals with an interest in children and adolescents, culture, and media.